KUSTOM KULTURE EVENT MARKETING AS A BRAND COMMUNITY CREATIVITY - Nashrudin Latif; Ferry Hariawan; Bayu Rama Laksono (Universitas Dinamika, 2021)
The purpose of this study is to describe kustom cultural events as a form of branding program from Retro Classic Cycles Jogjakarta and House of Customland Surabaya. During the event, we saw a touch of creative creation of the kustom kulture brand community. This study uses a qualitative method. Data were obtained based on observations and interviews with several people involved in the annual kustom kulture event. In addition, the researcher also developed data collection by looking at the social media managers of Retro Classic Cycles and House of Customland. Research findings show that there are efforts to develop brand communities, initiators routinely carry out annual activities in kustom cultural events. The kustom kulture event presents creative culture from a variety of artistic collaborators, both fine art and motor builder, which inclusively makes event collaborators really enjoy and actively participate in displaying their artworks as a medium for creativity exhibitions. Originality shows that kustom culture events are used as community media for kustom culture activists Retro Classic Cycles and House of Customland, as an effective way to build a certain identity of a community, so as to increase public knowledge about kustom kulture. Therefore, the quality and quantity of kustom cultural events can be increased according to the differences and novelty of the theme of the event being held.